Ligament Origins Are Preserved in Distal Radial Intraarticular Two-Part Fractures: A Computed Tomography-Based Study - Bain, Gregory Ian (Thieme Medical Publishers, 2013)
Background Operative fixation of intraarticular distal radius fractures is increasingly common. A greater understanding of fracture patterns will aid surgical fixation strategy. Previous studies have suggested that ligamentous insertions may less commonly be involved, but these have included heterogeneous groups of fractures and have not addressed Lister's tubercle. Purpose We hypothesize that fracture lines of distal radial intraarticular 2-part fractures have reproducible patterns. They propagate through the cortical bone between ligament origins and do not involve Lister's tubercle. Methods Axial CT scans of two-part intraarticular distal radius fractures were assessed independently by two examiners. The fractures were mapped onto a grid and the cortical breaches expressed as a percentile of the total radial width or length. The cortical breaches were compared with the ligamentous insertions on the distal and Lister's tubercle. Associated injuries were also documented. Results The cortical breaches occurred between the ligamentous insertions in 85%. Lister's tubercle was not involved in 95% of the fractures. Three major fracture patterns emerged: radial styloid, dorsal, and volar. Each major pattern had two subtypes. Associated injuries were common. Scapholunate dissociation was associated with all types, not just the radial styloid fracture pattern. Conclusions The fracture patterns of two-part intraarticular fractures mostly involved the interligamentous zones. Three major groups were identified: dorsal, volar, and radial styloid. Lister's tubercle was preserved with fractures tending to propagate radial or ulnar to this structure. We suggest conceptualizing fracture fragments as osseo-ligamentous units to aid prediction of fracture patterns and associated injury. Study Design Diagnostic III Level of Evidence 3